Step-by-step explanation
We are required to determine the correlation coefficient (r) of the data provided. This should be calculated with the formula:
![r_(xy)=\frac{\sum_{i\mathop{=}1}^n(x_i-\bar{x})(y_i-\bar{y})}{\sqrt{\sum_{i\mathop{=}1}^n(x_i-\bar{x})^2\sum_{i\mathop{=}1}^n(y_i-\bar{y})^2}}](https://img.qammunity.org/2023/formulas/mathematics/college/hexlqrz4rnescccrz3vrcilca7auwnj2dl.png)
The information can be represented in a table as:
From the table, we have:
![\begin{gathered} \sum_{i\mathop{=}1}^n(X-M_X)(Y-M_Y)=\sum_{i\mathop{=}1}^n(x_i-\bar{x})(y_i-\bar{y})=31.800 \\ \\ \sum_{i\mathop{=}1}^n(X-M_X)^2=\sum_{i\mathop{=}1}^n(x-\bar{x})^2=288.438 \\ \\ \sum_{i\mathop{=}1}^n(Y-M_Y)^2=\sum_{i\mathop{=}1}^n(y-\bar{y})^2=4.520 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/umxmyvmrz8ax68jvvpx00lfr2tquijj2rc.png)
Therefore, we can calculate the correlation coefficient as:
![\begin{gathered} r_(xy)=\frac{\sum_{i\mathop{=}1}^n(x_i-\bar{x})(y_i-\bar{y})}{\sqrt{\sum_{i\mathop{=}1}^n(x_i-\bar{x})_{i\mathop{=}1}^(2\sum n)(y_i-\bar{y})}}\frac{}{} \\ \\ r_(xy)=(31.800)/(√(288.438*4.520)) \\ \\ r_(xy)=0.8807 \\ \\ r_(xy)\approx0.88 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b73ddy2zdfz0dtou0ak3ywvewk3kq118x3.png)
Hence, the answer is 0.88.